Enlarged thyroidectomy in differentiated thyroid carcinomas with visceral invasion of neck - Perdomo, Roberto; Bertullo, Hugo; Ponasso, Hebe; Garra, Pedro; Blasiak, José; Alonso, Justo; Reissenweber, Nelson (Cirugía del Uruguay, 1979)
Presentation of case material consisting of three patients, leads to a review of differenciated thyroid carcinomas ( DTC) with invasion of visceral axis of neck. Due to the fact that respiratory obstruction has an important incidence in DTC death - rate, and because these tumors ha< e low evolutive potential, it is reasonable to conclude that decisive action in favour of complete exeresis -including portions of visceral axisis fully justified. This fact is reinforced by the good long - term evolution of patients so treated. Analysis of usual characteristics of these invasive carcinomas comprises different aspects of tactic and technical interest, applicable to surgical treatment as outlined.